The Influence of E-Service Quality, E-Word of Mouth, and Customer Experience on Purchase Decisions of Sociolla Products (A Study on SOCO by Sociolla Application Users in Malang) - Muthofi’in, Syifa Haniatul; Anastuti, Karina Utami (CV. Proaksara Global Transeduka, 2025)
This research aimed to examine the impact of e-service quality, e-word of mouth, and customer experience on purchase decisions. The study employed quantitative methodology with purposive sampling techniques. The sample consisted of 100 consumers who utilize the SOCO by Sociolla application in Malang. Findings reveal that E-Service Quality (X1) and Customer Experience (X3) variables individually demonstrate significant effects on Purchase Decisions (Y), whereas E-Word of Mouth shows no significant partial influence on Purchase Decisions (Y). The F test results indicate Fvalue exceeds Ftable (65.906 > 3.09) with significance below 0.05 (0.00 < 0.05). The coefficient of determination demonstrates that E-Service Quality, E-Word of Mouth, and Customer Experience variables collectively affect the Purchase Decision variable by 67.3%, with the remaining 32.7% attributed to other factors not examined in this research.